Digital Kenya An Entrepreneurial Revolution in the Making - Ndemo, Bitange; Weiss, Tim (Palgrave Studies of Entrepreneurship in Africa,, 2017)
This book is open access under a CC BY 4.0 license. Presenting rigorous and original research, this volume offers key insights into the historical, cultural, social, economic and political forces at play in the creation of world-class ICT innovations in Kenya. Following the arrival of fiber-optic cables in 2009, Digital Kenya examines why the initial entrepreneurial spirit and digital revolution has begun to falter despite support from motivated entrepreneurs, international investors, policy experts and others. Written by engaged scholars and professionals in the field, the book offers 15 eye-opening chapters and 14 one-on-one conversations with entrepreneurs and investors to ask why establishing ICT start-ups on a continental and global scale remains a challenge on the "Silicon Savannah". The authors present evidence-based recommendations to help Kenya to continue producing globally impactful  ICT innovations that improve the lives of those still waiting on the side-lines, and to inspire other nations to do the same. .